Evaluation of the Implementation of the Family Hope Program (PKH) in Poverty Alleviation - ANDAYANA, Made N D (PT. Keberlanjutan Strategis Indonesia, 2023)
Purpose: This research aims to determine the results of implementing PKH in 2023 through evaluating government policies. This research interviewed 12 informants with the criteria of sub-district secretaries, PKH assistants, and PKH recipients. Methodology: The method used is a qualitative method with a purposive sampling technique. Primary data was collected through interviews and face-to-face observations, while secondary data came from online sources, Social Service documents, and BPS. The analysis uses the Miles & Huberman model with data reduction, coding, and triangulation to ensure the reliability and validity of the information. Findings: The findings show that PKH in Lasiana Village has been running well and achieved its goals. The indicators include (1) effectiveness seen from participants maintaining their commitments and obligations; (2) the community receives the responsiveness of the program; (3) efficiency seen from the efficient disbursement process that is already running; (4) sufficiency has not been running well because the assistance received by the community sometimes runs out prematurely. (5) accuracy is appropriate because determining participants goes through many stages. Implication: This research discusses increasing access to quality health education services and improving economic conditions. The limitation of this research was that it was only carried out in one sub-district.